A Unified Approach to Mono- and 2,3-Disubstituted N–H Indoles - Kim, Ju Hee; Lee, Sun A; Jeon, Tae Sik; Cha, Jin Kun; Kim, Young Gyu (Synlett, 2023)
A unified approach to mono- and disubstituted N–H indoles is described by means of oxidative cyclization of 2-alkenyl anilines, which are prepared by cross-coupling of the corresponding o-bromoanilines. This procedure is operationally expedient and tolerant of common functional groups to allow regiospecific installation of the alkyl and aryl substituents.
Keywords: indoles; 2-alkenylanilines; hypervalent iodines; iminoiodinanes; phenylnitrenes